Enhancing Employee Performance Through Training : A Conceptual Review and Strategic Recommendations (International Journal of Scientific Research in Science and Technology, 2024)
The performance of an organization’s employees is directly indicative of whether or not the organisation will be successful. Employees are the backbone of any business. Taking this into consideration, upper management is boosting their investments in training and development programs in order to boost the productivity of their personnel. The purpose of this conceptual study is to investigate the impact that training has on employee performance and to make ideas for enhancing the effectiveness of training opportunities. By utilising a qualitative research methodology, the study examines previously published material as well as a number of case studies in order to emphasise the significance of training in the process of workforce development. The theoretical frameworks and models that are associated with employee training and the impact that it has on performance are investigated further below. The study provides a systematic checklist for top management to use in order to evaluate employee performance, diagnose underlying performance concerns, and create focused training programs in order to effectively address these issues. This proposal is based on the comprehensive analysis of the relevant literature. On the other hand, one of the most significant limitations of this study is that it does not provide any direct empirical evidence that has established a definitive association between employee performance and training. Since this is the case, the focus of future research ought to be on conducting empirical investigations in order to validate the association. This article provides a basic summary of the effectiveness of training, with a particular emphasis on the role that training plays in improving employee performance. In its conclusion, it makes suggestions for additional research and advocates for multi-level studies in order to gain a more in-depth understanding of training procedures and the impact they have on labour productivity.